Population Structure and Productivity of Pigs in Waroki Village, West Nabire District, Nabire Regency - Palenga, Nurlaila Susilawati; Dogomo, Emanuel; Dogomo, Ferdinan (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This study aimed to determine the population structure and productivity of pigs in Waroki Village, West Nabire District, Nabire Regency. Results showed that the most common number of pigs owned was 1-5 (74.55%). The sex ratio was 41.39% to 58.61%. The male pig population comprised 154 (41.39%), with 8.87% adults, 12.90% young, and 19.62% kids. The female pig population comprised 218 (58.61%), with 17.20% adults, 19.63% young, and 21.78% kids. Pig productivity was low, with a litter size of 6-10 pigs at 70.31% and a mortality rate of 1-2 pigs at 71.88%.